Effect of a Corrective Exercise Program on the Electrical Muscle Activity in Children With Forward Head Posture during Typing - Amirali Jafarnezhadgro; Jaber Khodapanah Ajirlou; Arefeh Mokhtari Malekabadi; Aidin Valizade-Orang (Shahid Beheshti University of Medical Sciences, 2021)
Background and Aims: Forward Head Posture (FHP) is one of the causes of cervical injury. The present study aims to evaluate the effect of a corrective exercise program on the electrical muscle activity in children with PHP during typing. Methods: This quasi-experimental study was conducted on 30 children with FHP aged 11-13 years (Mean ±SD height=153.38±1.51 cm, Mean ±SD weight= 52.51±40.1 kg). To record the electrical activity of the muscles, a electromyography system was used. For statistical analysis, the two-way ANOVA was used. For all statistical analyses, the significance level was set at 0.05. Results: In the exercise group, the post-test frequency spectrum in the levator scapulae and middle deltoid over the first and last 10 seconds of typing and in the sternocleidomastoid muscle in the final 10 seconds of typing were significantly different compared to the pre-test score. Conclusion: The corrective exercise program can affect the frequency spectrum of the electrical muscle activity in children with FHP, which can prevent from early fatigue in the muscles.